Arte e verdade em Hegel e o pluralismo estético contemporâneo - Cláudia de Campos Almeida (2020)
Hegel does not offer a concept of art. Rather, he postulates comprehensive determinations that emphasize art in its historical and philosophical significance. To establish the beauty of art is to establish its quality as a work of art. This means that the task of art is not to be beautiful, but to be a spiritual and cultural activity. With these questions in mind, the dissertation proposes to understand and insert contemporary art, with its plural aesthetic, as the culmination of the historical process of art foreseen by Hegel as a phenomenon that arises from the sensitive and material, but which develops dialectically for the conceptual and reflective. For this, I present two arguments: the spiritual nature of art, which gives Hegel's aesthetics a permanent status of updating; and the universalization of the principle of the artist's free creative subjectivity. Contemporary art, by radicalizing the displacement of the experience of art from meaning to thought, distances itself (apparently) from its genuine vocation in Hegelian aesthetics, which is to bring awareness to human truths in the very body of the work, that is, in its intuitive form. In practical terms, it reflects the current context in which, although the plural identity of the artistic object is already established, the public's bewilderment in the face of the diversity of works that require an accurate aesthetic judgment is still common. In contemporary art, the conciliation in the artistic object of the different aspects and determinations of reality, representing the concept of ideal and beauty in Hegel, does not depend on the external correspondence of the image with the spiritual and collective, but on the intellectual conscience that, in the final analysis, is willing to communicate with the body of the art work.